THE INFLUENCE OF A REVIEW TASK-BASED LITERACY LEARNING APPROACH ON STUDENTS' READING COMPREHENSION INTEREST AND LEARNING OUTCOMES - Nasyrah, Nasyrah; Syamsuri, Andi Sukri; Arief, Tarman A (Fakultas Keguruan dan Ilmu Pendidikan Universitas Muhammadiyah Luwuk, 2023)
The aim of the research is to determine the effect of implementing review assignment-based literacy learning on reading comprehension learning outcomes for class V students at UPT SDN 1 Enrekang. This type of research is an equation experiment with a one-group pretest-posttest design. The data collection methods used are learning outcomes tests to measure learning outcomes in reading comprehension, questionnaires to measure students' reading interest, and documentation. The data analysis techniques used are descriptive statistical approaches and inferential analysis. The results of the research on the application of review assignment-based literacy learning with a significance value of reading interest of 0.000 is smaller than 0.05 with the decision that there is an influence of the application of review assignment-based literacy learning to increase reading interest in class V students and the significance value of reading comprehension learning outcomes is 0.000 smaller than 0.05 with the decision that there is an influence of implementing review assignment-based literacy learning to improve reading comprehension learning outcomes in fifth grade students